An AI-driven framework for sustainable cultural communication: mechanisms, innovations, and synergy - Zhu, Boyi; Yu, Yu; Xu, Ruiyang (Frontiers in Communication, 2026)
With the rapid advancement of artificial intelligence (AI) technology, its driving role in sustainable cultural communication has become increasingly prominent. This study systematically explores the intrinsic mechanisms, innovation pathways, and synergistic effects of AI-driven sustainable cultural communication. The findings demonstrate that through technical mechanisms such as data intelligence, cross-modal interaction, and scenario perception, AI profoundly reshapes the production methods, content forms, and reception experiences of sustainable cultural communication. It has developed innovative practices in sustainable cultural communication through pathways that include the digital reconstruction of cultural resources, the innovation of content production paradigms, and the intelligent reconstruction of communication channels. On this basis, AI has further fostered multi-level synergistic effects in the process of sustainable cultural communication, namely internal resource optimization, external network effects, and social value co-creation. Finally, this study examines the ethical challenges and governance pathways of AI-driven sustainable cultural communication, offering a theoretical framework and practical reference for understanding the emerging landscape of sustainable cultural communication in the AI era.